A Young Lady with Acute Pulmonary Embolism after Caesarean Section - A Case Report - Taimur, Syed Dawood Md.; Haq, M Maksumul; Khan, Saidur Rahman; Kabir, CM Shaheen; Rahman, Hasanur; Karim, Md. Rezaul; Gomes, Hemanta I; Salahuddin, Md. (BIRDEM Medical Journal, 2013)
The presentation of acute dyspnea after pregnancy is rare, but should bring a number of important conditions to the mind of the attending physician. Pulmonary embolism, amniotic fluid embolism, pneumonia,aspiration pneumonia and pulmonary edema are some of the potentially devastating causes that must be considered. We report a 29 years young lady who presented with progressive severe dyspnoea, haemoptysis with right leg swelling and H/O lower uteraine caesarean section(LUCS) followed by mymectomy one and half months back , initially her ECG, chest X-ray & echocardiographic findings revealed evidence of pulmonary embolism we treated her with dramatic improvement. Birdem Med J 2013; 3(2): 116-120 DOI: http://dx.doi.org/10.3329/birdem.v3i2.17218